2021
DOI: 10.3389/fnins.2021.773694
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Speech Perception of Mandarin-Speaking Children With Cochlear Implantation

Abstract: Objective: This paper reviewed the literature on the development of and factors affecting speech perception of Mandarin-speaking children with cochlear implantation (CI). We also summarized speech outcome measures in standard Mandarin for evaluating auditory and speech perception of children with CI.Method: A comprehensive search of Google Scholar and PubMed was conducted from March to June 2021. Search terms used were speech perception/lexical tone recognition/auditory perception AND cochlear implant AND Mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Considering the complex characteristics in pitch and durational patterns, early implantation and sufficient CI experience are recommended to facilitate the acquisition and production of Mandarin by children with CIs [Zhou et al, 2013;Tang et al, 2021]. However, a related study only examined the effect of unilateral CI or bimodal stimulation in this population [Gao et al, 2021], and only one study reported the development of early auditory skills in 19 children with simultaneous bilateral CIs [Long et al, 2018]. To our knowledge, this is the first study to investigate the benefit of sequential bilateral cochlear implantation in children speaking Mandarin.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complex characteristics in pitch and durational patterns, early implantation and sufficient CI experience are recommended to facilitate the acquisition and production of Mandarin by children with CIs [Zhou et al, 2013;Tang et al, 2021]. However, a related study only examined the effect of unilateral CI or bimodal stimulation in this population [Gao et al, 2021], and only one study reported the development of early auditory skills in 19 children with simultaneous bilateral CIs [Long et al, 2018]. To our knowledge, this is the first study to investigate the benefit of sequential bilateral cochlear implantation in children speaking Mandarin.…”
Section: Discussionmentioning
confidence: 99%
“…When conventional BCD was first created in the early 20 th century, it was transcutaneous [18]. Regardless of the degree and type of hearing loss, all implant patients display a broad range of speech perception abilities, with various variables discovered to determine clinical performance [19].…”
Section: Introductionmentioning
confidence: 99%
“…A body of studies evaluated lexical tone performance in Mandarin-speaking CI users, which consistently demonstrated remarkable deficits in their tonal perception and production (Tan et al 2016; Chen & Wong 2017; Gao et al 2021 for reviews). It is noticeable that recognition of naturally spoken Mandarin tones in quiet can be relatively robust in CI users, with an average accuracy of above 75% (Peng et al 2004; Tao et al 2015; Zhang et al 2020a), possibly due to the available duration and intensity cues that co-vary with F0 contour.…”
Section: Introductionmentioning
confidence: 99%
“…It is a fundamental mechanism underlying the phonetic categorization, which is strongly influenced by listener’s native language experience and auditory deprivation (Harnad 2003; Goldstone & Hendrickson 2010; Zhang 2016 for reviews). Encumbered by auditory deprivations in early life and CI device-related limitations in pitch encoding, kindergarteners with CIs encounter consistent difficultly in lexical tone development that waits for promotion via efficacious interventions (Tan et al 2016; Gao et al 2021 for reviews). In a nutshell, the classical CP paradigm provides an ideal stringent test for the pediatric CI users to assess the training-induced benefits on pitch perception of Mandarin tones in terms of generalizability and sustainability.…”
Section: Introductionmentioning
confidence: 99%